2021
DOI: 10.1002/jum.15874
|View full text |Cite
|
Sign up to set email alerts
|

The AIUM Practice Parameter for the Performance of an Ultrasound Examination of the Abdomen and/or Retroperitoneum

Abstract: This parameter was developed by the AIUM in collaboration with the American College of Radiology (ACR), the Society for Pediatric Radiology (SPR), and the Society of Radiologists in Ultrasound (SRU). We are indebted to the many volunteers who contributed their time, knowledge, and energy to developing this document.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The results of this study may be affected by breathing and Valsalva techniques sometimes used in abdominal CT imaging, which possibly distort abdominal anatomy [15]. While this study did not investigate which breathing techniques were used and when, these breathing techniques are already adopted in the setting of ultrasound to aid in the localization of abdominal anatomy [16].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The results of this study may be affected by breathing and Valsalva techniques sometimes used in abdominal CT imaging, which possibly distort abdominal anatomy [15]. While this study did not investigate which breathing techniques were used and when, these breathing techniques are already adopted in the setting of ultrasound to aid in the localization of abdominal anatomy [16].…”
Section: Discussionmentioning
confidence: 94%
“…Current ultrasound protocols vary in their instruction for where to begin scanning the gallbladder, and many do not mention the possibility of taking an intercostal approach [6,[16][17][18]. The knowledge of these anatomical considerations of the gallbladder creates an opportunity to improve the education of ultrasound novices, who may now have a more specific understanding of where to begin when performing gallbladder sonography and ultrasound-guided procedures.…”
Section: Discussionmentioning
confidence: 99%
“…MFI showed good diagnostic performance (AUC: 0.94, 95% CI: 0.89–0.99) in identifying participants with stages I–II MN. A previous study has indicated that kidney length is commonly used for clinical monitoring of kidney damage ( 29 ). Yaprak et al measured the renal cortical thickness of 120 patients with CKD stages 1–5, and the results showed that the thickness of the renal cortex was positively correlated with eGFR ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Scanning for UAA and IVC was performed according to the guidelines of AIUM’s guidelines. 19 When the probe was in a longitudinal orientation high in the epigastrium, using the liver as a sonographic window, UAA was identified on the volunteer’s left and IVC on the volunteer’s right anterior to a vertebral body. Scanning was performed with quiet respiration.…”
Section: Methodsmentioning
confidence: 99%